Late cretaceous dinosaurs from the James Ross Basin, West Antarctica - Reguero, Marcelo Alfredo; Tambussi, Claudia Patricia; Coria, Rodolfo Anibal; Marenssi, Sergio Alfredo (Geological Society, London, Special Publications)
The fossil record of terrestrial vertebrates from the Late Cretaceous of Antarctica is currently composed of non-avian and avian dinosaurs from the marine sediments of the James Ross Basin, Antarctic Peninsula (West Antarctica). Although two dinosaurian formational assemblages (Late Campanian/Early Maastrichtian and Late Maastrichtian) are known, the record is still scattered, and evolutionary scenarios are tentative. Ten non-avian dinosaurs have been reported from Coniacian to Maastrichtian deposits, along with possible sauropod footprints of Early Maastrichtian age from Snow Hill Island. Five avian dinosaurs have been recorded or described exclusively from the Maastrichtian. The presence of an advanced titanosaur with characteristic procoelous mid-caudal vertebrae in Snow Hill Island Formation at Santa Marta Cove implies that the group achieved a global distribution by the Late Campanian. The Late Campanian/Early Maastrichtian non-avian dinosaur (ankylosaurs, ornithopods and dromaeosaurid theropods) clades probably attained a near-cosmopolitan distribution before the Late Cretaceous, and some aspects of this hallmark 'Gondwanan' fauna may therefore reflect climate-driven provinciality, not vicariant evolution driven by continental fragmentation. Antarctic Late Cretaceous avian dinosaurs are rare. They are restricted to the Maastrichtian and consist of a cariamid?, gaviids, a charadriiform and the basal Anseriformes Vegavis, and provide the first strong evidence for a basal radiation of birds known to exist in the Cretaceous. Fil: Reguero, Marcelo Alfredo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Tambussi, Claudia Patricia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones en Ciencias de la Tierra. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y ...